El cartel de cine hoy - Pérez Rufí, José Patricio (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2011)
The movie poster has been created as a way to promote a film that remains current, so its perpetuity hasn’t been discussed. Nevertheless, this advertising format has reduced the relevance compared to previous times. The mentioned integration in a campaign has caused equally changes in its function and in its own components, turned into a graphical reference for a multimedia advertising campaign. Movie posters take new form to express and change their definition being digitalized and adapted to the screen, as a way to access it. The rejuvenating of the meaning and forms of the movie poster achieved by this research take us finally to analyze the current trends in composition and graphic design: the movie poster seems to hollow superfluous elements that could create confusion, to focus on the power brought by the minimum of components, creating what we have named the minimal movie poster.